Derterminación del grado de madurez en la gestión de proyectos de TELMACOM LTDA. bajo el estándar metodológico del PMI® (2013)
The Colombian companies that provide engineering services are implementing best practices in the integral management of projects, in order to improve their processes and obtain the results expected by the interested parties. The project consists in the determination of the degree of maturity in the project management of TELMACOM LTDA., Under the methodological standard of the PMI®. The foregoing is based on the fact that the company under study recognizes having strong weaknesses when planning, executing and finalizing its projects. The management of projects has become methodological practices of great importance for this type of companies, highlighting the different needs that organizations show when they recognize that the management of projects they have presents problems and strong weaknesses when it comes to development and final achievement of your services, products or projects. In the sector of engineering construction companies, the integral management of projects is not efficiently developed, where this practice is not executed under any guidelines or standards, thus demonstrating little commitment to meeting the needs of the companies. clients, represented in deficient projects, with absences of planning for their execution, evident on costs, and deficient quality in the final product or service developed in some cases. In accordance with the above, the vast majority of companies in the sector show a lack of organizational culture in relation to the implementation of methodologies or project management standards, in order to generate in organizations a higher level of skills, commitment integral with the projects and the expectant needs of the clients. The general objective of this study is to diagnose the degree of maturity and determine the level of perception in the organizational management of projects Telmacom Ltda., Using as a tool the methodological standard proposed by OPM3®, proposing as products of analysis and diagnosis a proposal both technical and administrative that allows the company to improve the current level of its project management. The study points out the following specific objectives to achieve:  Identify the degree of compliance with the best practices associated with the SMCI category (standardization, measurement, control and improvement),  Identify, through the use of the methodological standard proposed by OPM3®, the degree of compliance in the methodology of processes of the Project domain, in accordance with the 9 areas of knowledge and 5 groups of processes. To elaborate in accordance with the results obtained a proposal of improvement at the level of maturity in the management of projects for the company, which will contain, among others, a technical proposal and an administrative proposal for the improvement of the maturity in the management of projects in Telmacom Ltda. The methodology used for the development of this study consisted of the collection and analysis of company information, as well as the preparation of fieldwork, which consisted in the presentation and global awareness of the purpose of the study to those involved in the company Telmacom Ltda. . Additionally, in order to conceptualize the interested parties, a training was held where the fundamental concepts of the OPM3® model of the PMI® will be presented. As a result of the exercise of the fieldwork, structured and completed interviews were obtained from the respondents selected by the company, which constitute the main information to continue with the development of the project, to determine the state in which the company is located. at the level of project management, as well as to have the starting point for the planning of the improvement proposal. The present work, is structured its chapter first by the Profile of the selected company object of the present study, which includes the general description and the profile of the company. In the second chapter is the theoretical framework consulted with reference to the conceptual foundations of the administration and project management of the Project Management Institute PMI®. Subsequently, in the third chapter, the maturity model in project management, OPM3®, is related. In the fourth chapter, the methodological development is carried out. Moving on to the fifth chapter, we present the analysis of results obtained from the study based on the interpretation of results and graphs constructed with the data obtained from the interviews. Finally, in the sixth chapter, a proposal for improvement at the level of maturity in the management of projects for companies is presented.